-7(2x+8)=-14x-56

Simple and best practice solution for -7(2x+8)=-14x-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2x+8)=-14x-56 equation:


Simplifying
-7(2x + 8) = -14x + -56

Reorder the terms:
-7(8 + 2x) = -14x + -56
(8 * -7 + 2x * -7) = -14x + -56
(-56 + -14x) = -14x + -56

Reorder the terms:
-56 + -14x = -56 + -14x

Add '56' to each side of the equation.
-56 + 56 + -14x = -56 + 56 + -14x

Combine like terms: -56 + 56 = 0
0 + -14x = -56 + 56 + -14x
-14x = -56 + 56 + -14x

Combine like terms: -56 + 56 = 0
-14x = 0 + -14x
-14x = -14x

Add '14x' to each side of the equation.
-14x + 14x = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4(b-1)+9=2(3b-4)+b | | 20x^2-52x-112=0 | | 6n-3=18 | | 11K=55 | | 15+1.25m= | | 72=-4d+8 | | 90=3x-10x+8 | | 0=-6x-15y | | 8x+5-4(x+1)=9x+5 | | (6a-5)=-4a | | 134+200-50= | | 18=7r-10 | | x-3(x-1)+12=35 | | 3x-1(x+4)=-x+8 | | Up+uv=t | | -55=4x+5(-x-13) | | 6y=5y | | X+3+x+3+(2x-6)+(2x-6)=26 | | X-18=37 | | 15d^2+16d-15= | | -14=b-3 | | (6a-5)=4a | | r=4+7x-sxfory | | -x+9-7x-11=14 | | 4x^2+15= | | 4(x+7)=-2(x-3)-8 | | 10(3x-4)=10 | | 28x+21=5x+20-6 | | 5y-18=-8 | | 68=-2x-4(1+4x) | | J-8=-12 | | 9x^2-97x+280=0 |

Equations solver categories